Tata Kelola Perencanaan Program Bantuan Sosial Lansia oleh BAPPEDA Kota Batam - Fera Kasmita; Okparizan .; Okky Rizki Azizi (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This study analyzes the planning governance of the Elderly Social Assistance Program by BAPPEDA of Batam City as part of poverty alleviation efforts, focusing on coordination between BAPPEDA and the Social Affairs Office and on supporting and inhibiting factors. A qualitative case study approach was employed. Data were collected through interviews with five informants from BAPPEDA and the Social Affairs Office and through documentation of the RPJMD, RKPD, Renstra, Renja, the National Single Socioeconomic Data (DTSEN), and related planning documents. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña and the Collaborative Governance framework of Ansell and Gash. The findings show that program planning is embedded in a structured local development planning mechanism. BAPPEDA acts as a planning coordinator and facilitator, while the Social Affairs Office performs technical functions. DTSEN, periodic verification, coordination forums, cascading of planning documents, and SIPD-RI support the planning process. Starting conditions, facilitative leadership, institutional design, face-to-face dialogue, trust building, commitment to process, shared understanding, and intermediate outcomes are visible, although the process is predominantly government-to-government coordination. Supporting factors include government commitment, inter-agency coordination, DTSEN, regulations, and information technology, while inhibiting factors include changing beneficiary data, population mobility, fiscal constraints, and administrative difficulties.